Toleransi di Kalangan Mahasantri dalam Menjalankan Moderasi Beragama di Lingkungan Ma’had Aly - Irfan Mas'ud Abdullah; Bambang Ruswandi; Fatihunnada Fatihunnada; Abdul Hakim Wahid (Refleksi, 2021)
Tolerance and accommodativeness to local culture among students in Ma'had 'Aly is very good and has a significant impact on proving the attitude of religious moderation. This can be seen from the loading factor value of the tolerance dimension with a value of (0.815) and the Local Culture Accommodative dimension (0.603). If the level of tolerance and accommodativeness to local culture is calculated to measure the level of religious moderation of students, then the views of students regarding religious moderation are on a scale of 73.42, which means they are in the moderate category. The sampling method used in this research is the method of purposive sampling and quota sampling. The purposive sampling method was used in the selection of three Ma'had Alys, namely Ma'had al-Jami'ah UIN Jakarta, Darus-Sunnah International Institute for Hadith Sciences, and Pesantren Luhur Sabilussalam. While the Quota Sampling method is used in the distribution of student selection samples. The number of samples used in this study were 120 students. The objects of this research are students who are spread across three Ma'had Alys, namely: Ma'had al-Jami'ah UIN Jakarta, Darus-Sunnah, and Pesantren Luhur Sabilussalam.